GENETIC DIVERSITY STUDIES IN SWEET CORN (Zea mays L. SACCHARATA.) - A.THANGA HEMAVATHY, (The Bioscan, 2020)
Assessment of genetic diversity is a pre-requisite to broaden the genetic background of cultivated base of sweet corn, an endosperm mutant of field corn that alters starch biosynthesis pathway in endosperm. In the current investigation, genetic divergence among 26 sweet corn inbred lines was assessed on the basis of eight agro- morphological traits, five quality parameters. Cluster analysis grouped the sweet corn genotypes into 12 clusters based on the degree of divergence between the genotypes.. Maximum number of five genotypes was grouped under cluster II, while clusters XI and XII forms solitary cluster with one genotype in each cluster and rest of the clusters had two genotypes each. Maximum inter cluster distance was observed between cluster III and cluster IX (162.866) followed by cluster VII and IX (157.555) and cluster IX and XII (153.969). The maximum intra cluster distance (95.812) was observed in cluster II followed by cluster X (81.552), cluster IX (77.475). Among the thirteen traits studied, maximum contribution was made by green cob yield per plant (41.23%) followed by sucrose (22.46%), starch (16.92%) and total carbohydrates (16.62%). The traits viz., green cob yield, sucrose, starch and total carbohydrates contributed 97.23 per cent towards total divergence. Therefore, these characters may be given importance during hybridization programme.